PENGARUH PRODUK DOMESTIK REGIONAL BRUTO DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI KOTA PRABUMULIH - Rika Rahmadina Putri; Mudzakir Ilyas; Taufik Rohman (Program Studi Perbankan Syariah, 2022)
This study aims to analyze the effect of Gross Regional Domestic Product (GRDP) and population on the poverty rate in Prabumulih City. The research data used is secondary time-series data for the period 2010-2021 obtained from the publication of the Prabumulih City Statistics Center (BPS). The regression model in this study is multiple linear regression analysis method and processed with the help of Statistical Package for the Social Sciences (SPSS) software. The results showed that GRDP and population together (simultaneously) had a significant effect on the poverty rate in Prabumulih City. Partially, GRDP has a negative and significant effect on the poverty rate, while population has a positive and insignificant effect on the poverty rate in Prabumulih City.